Integrated Circular Farming and Supply Chain for Rural Economic Community Resilience - Sirajuddin, Sirajuddin; Sutisna, Tatang; Hilal, Samsu; Ridwan, Asep; Nasifah, Ainun (Indonesian Journal of Sustainability Accounting and Management, 2025)
Establishing a sustainable economy to ensure food security in rural communities presents a significant challenge amid global economic instability and the threat of a food crisis. Integrated supply chains and circular economy models have emerged as strategies to enhance economic resilience. However, their application in rural agricultural communities is still limited. This study addresses this gap by developing an integrated supply chain and circular economy principles to strengthen the economic resilience of rural communities. Using a system thinking approach and Powersim software, the study simulates and quantifies the model’s impact. Simulation results show that 1 hectare can produce 45,300 kg of sorghum per harvest, or 122,310 kg/year. This output can produce 13,590 kg of sorghum grain, 110,079 kg of silage, 44,032 kg of manure, and 30,822 kg of organic fertilizer. The integrated system generates gross annual revenues of 38,240 and incurs 26,243 in operating costs, resulting in a yearly net profit of 11,996. Financial analysis reveals a net present value (NPV) of 124 in the third year, a 10% internal rate of return (IRR), and a payback period (PBP) of 2.48 years. These findings highlight the potential of integrated agricultural systems in promoting rural economic resilience and sustainable farming practices.